Ear characters of maize cultivars in green stadium - Oliveira, Luiz Antonio A. de; Groszman, Américo; Costa, Renato Alves da (Pesquisa Agropecuaria Brasileira, 2014)
A preliminary experiment was carried out in Campos, Rio de Janeiro State, Brazil, aiming to evaluate the performance of maize (Zea mays L.) cultivars in the green stadium. Relationships among characters were studied: ear length with husk and ear weight without husk related to six other ear characters. Ear weight without husk, which is a desireable commercial characteristic of green maize for supermarket purpose, was influenced (R2 = 0.870) by ear length with husk, ear length without husk and ear diameter. However, the highest r values were given by ear length without husk and ear weight with husk. Ear length with husk, a desireable characteristic of green maize when commercial destination is for markets and shops, was influenced (R2 0.572) by ear length without husk and ear diameter. The highest r values were given by ear weight with husk and ear diameter. For Market destination such as fairs and shops, the hybrids Ag 301, Ag 163, C 111, C 521, C 522, C115, C 201 and C 125 presented the best performances. When the market destination is supermarkets, the best choices were the hybrids C 521, C 203, C 511, C 317 and Ag 162. As far as the number of normal ears, C 317, C 111, Sintético Pesagro-Rio and C 125 were the best hybrids.